2018
DOI: 10.1088/1361-665x/aab27b
|View full text |Cite
|
Sign up to set email alerts
|

Research on the vibration transmissibility of impedance modulating structure based on magnetorheological fluid

Abstract: Due to the fact that wave propagation has superior penetration at low frequencies, its attenuation in a limited range is a challenge. To solve this issue, a novel impedance modulating structure based on magnetorheological (MR) fluid is proposed, and the vibration transmissibility of the proposed structure is investigated. The modulation of impedance is realized by controlling the applied magnetic field, which can result in liquid-solid conversion of MR fluid. The wave equation in MR fluid is established based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The results show that the gradient plate can significantly reduce sound power more than an isotropic plate. Liu et al [12] and Si et al [13] constructed an impedance-layered structure. They studied its vibration transfer characteristics by controlling the MRF impedance through an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the gradient plate can significantly reduce sound power more than an isotropic plate. Liu et al [12] and Si et al [13] constructed an impedance-layered structure. They studied its vibration transfer characteristics by controlling the MRF impedance through an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Si et al [8] constructed a quasi-periodic structure using MRF by changing the thickness and arrangement of the MRF's high and low impedance layers and investigated its vibration transfer characteristics, and found that the quasi-periodic structure has better vibration attenuation in a specific frequency range. Liu et al [9] and Zhao et al [7,10] built a modulable impedance structure based on the rheological properties of the MRF, equated the MRF to a saturated porous medium using Biot theory and equivalent medium theory, established the transmission model of elastic waves in the modulable impedance structure and solved it numerically. The results show that the propagation and attenuation of elastic waves can be effectively controlled by modulating the impedance of MRF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to MRF dampers, the vibration-suppressing performance of MRF-based structures under an external magnetic field has been extensively investigated. Liu et al [ 10 ] proposed an impedance modulating structure based on the MRF and studied its vibration transmissibility. The results showed that the modulation of MRF impedance validly showed excellent attenuation for wave propagation.…”
Section: Introductionmentioning
confidence: 99%